2010
DOI: 10.1111/j.1365-2435.2009.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Fattening strategies of wintering great tits support the optimal body mass hypothesis under conditions of extremely low ambient temperature

Abstract: 1. In a seasonal environment, subcutaneous energy reserves of resident animals often increase in winter and decline again in summer reflecting gradual seasonal changes in their fattening strategies. We studied changes in body reserves of wintering great tits in relation to their dominance status under two contrasting temperature regimes to see whether individuals are capable of optimizing their body mass even under extreme environmental conditions. 2. We predicted that dominant individuals will carry a lesser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 57 publications
2
73
1
Order By: Relevance
“…It is important, however, to interpret our results in the context of the specific environmental stressor. The average minimum winter temperature in Daugavpils is− 9.7°C (http://www.world-climates.com/city-climatedaugavpils-latvia-europe/), and conditions in the weeks before and after the extreme cold spell in 2009/2010 were relatively stable, consistent with previous years and without warning of the low temperatures to come (Krams et al 2010). The trade-off between breast stripe area and survival, then, may be specific to extreme conditions.…”
Section: Discussionmentioning
confidence: 67%
“…It is important, however, to interpret our results in the context of the specific environmental stressor. The average minimum winter temperature in Daugavpils is− 9.7°C (http://www.world-climates.com/city-climatedaugavpils-latvia-europe/), and conditions in the weeks before and after the extreme cold spell in 2009/2010 were relatively stable, consistent with previous years and without warning of the low temperatures to come (Krams et al 2010). The trade-off between breast stripe area and survival, then, may be specific to extreme conditions.…”
Section: Discussionmentioning
confidence: 67%
“…2), implying implies that the level of hypothermia in wintering birds is not only determined by spatiotemporal and climatic parameters (e.g., Nord et al 2009) but also by the physical state of the individual (Reinertsen and Haftorn 1984). Since the amount of subcutaneous fat reserves in wintering birds may co-vary with social status (Broggi et al 2003;Krams et al 2010), the positive relationship between T b and fatness index might indicate that thermoregulatory strategies diVer between dominant and subdominant blue tits. However, this idea remains elusive because we have no empirical data on the dominance of the birds included in this study.…”
Section: Discussionmentioning
confidence: 94%
“…The Great Tit is a small non-hoarding passerine that stores the acquired fat reserves internally in order to fuel thermoregulatory and other metabolic needs. Several studies have shown that in Great Tits males always dominate females and, within the sexes, adults dominate juveniles (Saitou 1979;De Laet 1985;Pöysä 1988;Sandell and Smith 1991;Gosler 1996;Verbeek et al 1996;Krams 1998aKrams , 2000Verbeek et al 1999) Since rank-related access to resources usually results in better winter survival rates among dominants (Ekman and Askenmo 1984;Krams et al 2001Krams et al , 2010Koivula et al 1995), we predicted a dominance rank-related increase in heterophil counts, decrease in lymphocyte counts, and increase the H/L ratios under conditions of extreme low ambient temperature. We expected higher H/L ratios in adult and, especially, juvenile female Great Tits under conditions of extremely low ambient temperature when the dominant individuals are most likely to take advantage of their superiority in access to resources.…”
Section: Introductionmentioning
confidence: 98%